Characterization of medical device constituents and development of duration-based non-cancer threshold of toxicological concern values - Taylor Builee; Todd A. Kennedy; Valériane Levelut; Megan A. Hahn; Stephen Bond; Michael K. Peterson; Frances K. Hsia; Alessia Stornetta; Kristin J. Erickson; Kimberly D. Ehman; Bindu Prabhakar; Bradford D. Bagley; et al. (Frontiers in Toxicology)
IntroductionIn the absence of sufficient constituent-specific dose-response toxicity data, threshold of toxicological concern (TTC) values are commonly used in toxicological risk assessment of medical device (MD) constituents. When experimental data or predictions suggest that a constituent is not likely to have genotoxic effects, categorizing the constituent into its appropriate Cramer Class and application of the corresponding TTC value is recommended. This paper presents the uniqueness of the MD chemical space when compared to the historical Munro TTC dataset via structure-based chemical taxonomy, ToxPrint chemotypes, physicochemical properties and molecular descriptors, and proposes duration-based MD non-cancer TTC values.MethodsMore than 15,000 MD constituents were identified and screened, and 790 constituents met the established criteria for inclusion. Constituents with chemotypes matching inorganic substances, metals, pharmacologically active, nitroso-like, aflatoxin-like, azoxy, benzidine, polyhalogenated dibenzodioxins, dibenzofurans, biphenyls, high molecular weight polymers, nanomaterials, proteins, and radioactive substances were excluded from the evaluation. Constituent-specific toxicity data were obtained from the data-rich and open-access, European Chemicals Agency Registration, Evaluation, Authorisation and Restriction of Chemicals (ECHA REACH) database. Considered protective for systemic, developmental, and reproductive toxicity, constituent-specific oral no-observed-adverse-effect-level (NOAEL) values from repeated dose studies with a reliability (Klimisch) score of 1 or 2 were selected as the point of departure (POD) for each duration (subacute/subchronic/chronic/lifetime). The NOAEL values selected as PODs for each constituent in each duration category were plotted using log-normally fitted cumulative frequency distributions, and an uncertainty factor of 100 (10 each for inter and intraspecies differences) was applied to the lowest fifth percentile NOAEL value extrapolated from each curve.ResultsThe resulting non-cancer TTC values for various exposure duration categories were 112 μg/kg/day for ≤ 1 day to 30 days, 111 μg/kg/day for 31 to 365 days and 41 μg/kg/day for ≥ 366 days.DiscussionThe proposed MD non-cancer TTC values followed the same approach as derivation of the Munro TTC values; however, they are derived exclusively from MD constituents with chemical-specific data for the appropriate period of assumed exposure to the constituent.